Սեբաստիայի 1562 թվականի խորհրդաժողովը և Աբգար դպիր Եվդոկացու բանագնացությունը - Պողոսյան, Արարատ քհն.
Regardless of the recorded results, the Council of Sebastia in 1562 is one of the most essential milestones in the Armenian national-liberation movement. The Council made it all-Armenian and formulated the idea of liberating the whole of Armenia. The pre-Soviet and post-Soviet publications regarding the Council are mostly one-sided and biased, therefore the history related to it should be revised and presented impartially. This article is an attempt to examine anew the information about the Catholicos Michael of Sebastia available in Armenian historiography, as well as to reconsider the issues regarding the reasons for convening the Council, its place and participants. It is important to state that those who convened the Council of Sebastia in 1562 were well aware of the geopolitical and religious situation, but they overestimated the capability of the foreign powers. The main novelty of the Council of 1562 was that, unlike the Council of Etchmiadzin in 1547, an objective was set to liberate not a particular part of Armenia, but the whole of Armenia. Церковный Собор в Себастии (1562 г.), независимо от результатов, является одной из важнейших вех армянской национально-освободительной борьбы, придавший ей общеармянский характер и сформулировавший идею полного освобождения Армении. Досоветские и постсоветские публикации о соборе, как правило, односторонни и предвзяты, поэтому его история нуждается в пересмотре. В статье делается попытка вновь сопоставить данные армянской историографии о католикосе Микаэле, а также рассмотреть вопросы о причинах созыва, месте и участниках собора. Важно отметить, что в 1562 г. приглашенные на встречу в Себастии были знакомы с геополитической и религиозной ситуацией, однако переоценивали возможности иностранных держав. Главной новостью собора в 1562 года было то, что, в отличие от Эчмиадзинского собора 1547 г., была поставлена задача освобождения не какойлибо части, а всей Армении.
Keywords: Հայոց պատմություն; Հայոց եկեղեցի